THE USE OF TRANSLATION IN TEACHING READING ANALYTICAL EXPOSITION TEXT - Siti Kholija Sitompul; Masitowarni Siregar; Anni Holila Pulungan (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
This study aimed at describing the use of translation and investigating the reasons of using translation in teaching reading analytical exposition text grade eleven at MAN Peanornor. This study was qualitatively conducted that taken 3 English teachers of MAN Peanornor. The data were collected by using an interview and observing the whole process of teaching reading analytical exposition text. The findings of this study showed that there were 51 times of using translation found during three processes that they were conveying and checking meaning of words or sentences, explaining grammar and classroom management. It was also found that the use of translation was used in the scientific approach activity that experimenting and associating activity were the dominant used rather than observing, questioning and communicating activity in teaching. The reasons of using translation in teaching reading analytical exposition text were facilitating communication, teacher-student relationship and the L2 learning. The findings of this study revealed that translation contributed to the study of foreign language teaching especially teaching reading skill. Keywords : translation, teaching and analytical exposition text.